Coopetition Strategy in Property Business – A Case Study on Corporations of Regional Real Estate Association - Katharina Priyatiningsih; Agus Rahayu; Disman Disman; Lili Adi Wibowo (Research Synergy Foundation, 2023)
The management of a real estate corporation wants to have a strategy to achieve effective and efficient performance with dynamic environmental conditions. The purpose of this study is to understand the strategy of coopetition, which is expected to answer the environmental dynamics of technological change and the corporation's ability to innovate. This study aims to determine the coopetition strategy that can be built in real estate companies from the influence of technological change as an external factor and the influence of innovation ability as an internal factor, so this research method uses a descriptive-explanation approach. Therefore, the research method is designed to describe and explain technological changes and innovation capabilities that affect the coopetition strategy. The research instrument was used to collect data through a multilevel scale, interviews, and observations from the analysis unit of property companies that are members of the real estate industry association. Data processing using PLS-SEM with a minimum sample of 10 times the maximum arrow pointing to the latent variable so that the minimum number of samples in this study was 20 samples, but for more precise data, it was enlarged to 32 samples. The research model using the hierarchical component model produces a total value of the effect on the coopetition strategy from a technological change of 0.617, while the innovation ability is 0.416. This finding shows that technological changes in the property industry are significant and more influential than innovation capabilities. Technological changes are also significant, with an effect of 0.458 on the ability to innovate. The coopetition strategy from the competitive aspect is most influenced by technological changes and innovation capabilities compared to the cooperative aspect. In the end, this research has technical limitations on the coverage of the project area and the domicile of the corporation in relation to the pandemic regulations that apply in the field; however, it is carried out according to scientific principles. The novelty of this research from previous research is that the strategy of coopetition in the property industry has not been studied in depth apart from taking into account the corporations.